Effectiveness of Ginger Warm Compress on Neck on Head Pain of Elderly Patients with Hypertension at UPTD Tresna Werdha Natar - Sutrisno; Antika, Rini; Ferlia, Reni; Hernanda, Rice (INDOGENIUS, 2025)
Background & Objective: To determine “The effectiveness of warm ginger compress on the neck on the head pain of elderly patients with hypertension at UPTD Tresna werdha natar”.   Method: This type of research is a quantitative study that utilizes a pre-experimental approach, with a pretest-posttest design and applies a sample selection technique through total sampling. The population and sample were all elderly patients with hypertension totaling 15 respondents, the tools used in this study were standard operating procedures (SOPs), the data analysis used was the Wilcoxon Test. Result: The results obtained based on statistical tests showed that there was an effect of using warm compresses made of ginger on reducing the level of pain in the head p-value 0.000. Conclusion: It is concluded that the use of warm compresses of ginger in the neck area can reduce the head pain of the elderly who experience hypertension.